Buckling Instability of Flexible Joint under High Pressure in Solid Rocket Motor - Wang Chunguang; Xu Guiyang; Gong Jianliang (International Journal of Aerospace Engineering)
Deflection torque decrease of flexible joint under increasing pressure was normally attributed to the changing shear stress and has not been carefully resolved, which was far from convincing. To systematically investigate the mechanism, the structure characteristics of the flexible joint were analysed under different pressures. It was found that the decrease in deflection torque of the flexible joint was mainly due to the buckling response when it bears the deflection and pressure at the same time. The Riks method was utilized in this paper with the simulation of the buckling process of the flexible joint by ABAQUS. The static Riks method and general method were applied, respectively, to simulate the different pressurization processes at different pre-angles to obtain the rules of swing angle changing with pressure. The spring torque under various pressures was obtained and had a good coherence with the test results. For industrial applications, the concept of container pressure torque and its formula were proposed in this study, which was demonstrated to be of high accuracy. The simulation method and conclusions in this paper will definitely provide the beneficial reference to the design of the flexible joint in high-pressure working environment.